Digestibilidade de dietas e metabolismo em frangos de corte e suínos alimentados com soja integral processada - Carvalho, Amanda D'ávila (2006)
The purpose of this dissertation was to realize two studies to evaluate the nutritional value of diets containing full-fat soybean processed by vacuum (FFSvac) or by steam (FFSstm) and of FFSvac and FFSstm for broilers and pigs. The study 1 evaluated the digestibility of diets, of soybeans and the metabolism of broilers fed with diets containing processed full-fat soybean. The experimental design was completely randomized with five treatments (control diet - CD, CD with isometric substitution of 40% FFSvac or FFSstm; diet with FFSvac and diet with FFSstm). The N intake was 23 and 20% less (P<0.01) to the broilers fed with diets containing FFSvac or FFSstm in relation to control group. The excretion, digestibility and absorption of N were not influenced (P>0.05) by the diets. The excretion of energy was 19 and 22% less (P<0.01) to the broilers fed with FFSvac in the diet in relation to control group and those fed with FFSstm in the diet. The diet with FFSvac enhanced (P<0.01) the digestibility and the metabolization of energy. The apparent metabolizable energy corrected for retention of N (MEn) was 12% higher (P<0.01) to the one fed of diet with FFSstm and similar to control diet. The dry matter, protein and ether extract digestibles, the apparent metabolizable energy and MEn were similar (P>0.05) for full-fat soybean processed by vacuum or by steam. The digestibility and absorption of N are not influenced by diets containing full-fat soybean processed by vacuum or by steam. The vacuum processing for full-fat soybean improves the digestibility of gross energy and the apparent metabolizable energy of diets. For the studied soybean types, the digestible nutrients, the apparent metabolizable energy and corrected to nitrogen retention are similar. The study 2 evaluated the digestibility of diets, of soybeans and the metabolism of pigs fed with diets containing processed full-fat soybean. The experimental design was completely randomized with five treatments (control diet - CD, CD with isometric substitution of 40% FFSvac or FFSstm; diet with FFSvac and diet with FFSstm) and four replications with one animal. The intake, urinary excretion of energy and digestible and metabolizable energy were not influenced (P>0.05) by the type of FFS processing. The animals fed diet containing FFSvac excreted 56% more energy (P<0.05) in their feces than animals fed the control diet. The digestion and N metabolism were not influenced (P>0.05) by the type of FFS processing. The digestibility of P, the fecal and the retained P did not differ (P>0.05) between the diets. For FFS, the digestible contents of protein and energy were 10.4 and 4.0% higher (P<0.01) with vacuum processing. The processed soybean does not affect the digestibility of diets neither the metabolism of pigs, except the digestibility of gross energy, which is reduced. The vacuum processing improves the digestible contents of protein and energy of full-fat soybean.